Magnetic composite material, preparation method and application thereof, electrochemical sensor and device

By using the core-shell structure of CoFe2O4@ZIF-67 as the electrode modification material, the problems of poor dispersion and stability of existing materials when electrochemically detecting lead ions are solved, and an electrochemical sensor with high sensitivity and anti-interference ability is realized.

CN119438339AActive Publication Date: 2025-02-14四川省市场监督管理局食品安全检查技术中心 +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411617921.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-14
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

The existing electrode modification materials have problems such as poor dispersion, easy aggregation after modification, poor acid and alkali stability and poor conductivity, resulting in insufficient sensitivity and stability in electrochemical detection of lead ions.

Method used

The core-shell structure of CoFe2O4@ZIF-67 is used as a magnetic composite material. The material is prepared by hydrothermal reaction and modified on the magnetic working electrode of the electrochemical sensor to increase the contact area with the electrolyte and provide more activity. center.

Benefits of technology

The detection sensitivity and anti-interference ability of the electrochemical sensor are improved, and lead ions can be specifically detected in the aqueous solution, and the stability and reproducibility are good.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119438339A_ABST
    Figure CN119438339A_ABST
Patent Text Reader

Abstract

The invention discloses a magnetic composite material, a preparation method and application thereof, an electrochemical sensor and a device. The magnetic composite material disclosed by the invention has a core-shell structure of CoFe2O4 and ZIF-67, the CoFe2O4 is a magnetic core body, and the ZIF-67 is a shell layer. Compared with an existing electrode modification material, the CoFe2O4-ZIF-67 magnetic composite material disclosed by the invention has a relatively large specific surface area, the contact area between the CoFe2O4-ZIF-67 magnetic composite material and an electrolyte can be effectively increased, and a richer active center is provided, so that the adsorption of lead ions is facilitated, the electrochemical performance is better improved, and the service life of the electrode modification material is prolonged. The constructed electrochemical sensor is high in detection sensitivity and strong in anti-interference capability, negative ions, positive ions and other impurities in a to-be-detected solution basically do not interfere with detection of the electrochemical sensor, and lead ions in an aqueous solution can be specifically detected.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemical detection technology, and in particular to a magnetic composite material, a preparation method and application thereof, an electrochemical sensor and a device thereof. Background Art

[0002] There are many harmful heavy metals in industrial wastewater, mainly including pollutants with high biological toxicity such as mercury, cadmium, chromium, lead, etc.; these heavy metals can enter the human body through the gastrointestinal tract, especially lead can be directly absorbed through the skin. After entering the human body, heavy metals will damage and affect cell function, thereby interfering with the central nervous system, causing mental disorders, destroying plasma material balance, and may damage important organs such as the lungs, liver, and kidneys, aggravating the underlying disease condition, and cannot be degraded in the body.

[0003] At present, the traditional detection methods for lead ions include atomic absorption spectroscopy, inductively coupled plasma mass spectrometry, X-ray fluorescence spectroscopy, etc. However, these methods are expensive, complicated, time-consuming, and cannot be monitored online. Therefore, the development of a fast, accurate, sensitive, and simple method for low-concentration lead ion detection has been an important research topic in recent years.

[0004] Compared with the above-mentioned traditional detection methods, electrochemical analysis has the advantages of simple equipment and easy automation, as well as fast response speed, low cost, good stability, strong selectivity and high sensitivity. Among them, the key to achieving high sensitivity and low detection limit detection lies in the modified material of the working electrode.

[0005] However, existing materials such as carbon nanotubes, graphene, nanometals and metal oxides used for electrode modification have problems such as poor dispersibility and easy aggregation after modification, or poor acid-base stability and low conductivity. Therefore, it is necessary to develop new modified electrode materials to improve the sensitivity and stability of electrochemical detection of lead. Summary of the invention

[0006] The present invention discloses a magnetic composite material and a preparation method and application thereof, an electrochemical sensor and a manufacturing method and device thereof, in order to solve the problems of poor dispersibility, easy aggregation after modification, poor acid-base stability, low conductivity and the like existing in materials such as carbon nanotubes, graphene, nanometals and metal oxides currently used for electrode modification.

[0007] In order to solve the above problems, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a magnetic composite material having a core-shell structure of CoFe2O4@ZIF-67, wherein CoFe2O4 is a magnetic core and ZIF-67 is a shell.

[0009] In a second aspect, the present invention provides a method for preparing the magnetic composite material, comprising the following steps:

[0010] (1) CoFe2O4 and dimethylimidazole are dispersed in a methanol solution to prepare a solution A; Co(NO3)2·6H2O is added to the methanol solution to prepare a solution B; and the solution B is then added dropwise to the solution A under stirring conditions to prepare a reaction solution C after being uniformly mixed;

[0011] (2) The reaction solution C is transferred to a reactor for hydrothermal reaction. After the reaction is completed, the reactor is naturally cooled to room temperature, and the precipitate is collected by magnetic separation; the precipitate is then washed with ethanol and dried to prepare the CoFe2O4@ZIF-67 composite material.

[0012] In a third aspect, the present invention provides an application of the magnetic composite material in lead ion detection.

[0013] Optionally, the magnetic composite material is used as an additive for the detection of lead ions, comprising the following steps: adding the magnetic composite material to a test liquid for mixing, turning on an electrochemical sensor after the magnetic composite material fully adsorbs the lead ions in the test liquid, the magnetic working electrode of the electrochemical sensor adsorbs and fixes the magnetic composite material adsorbed with lead ions on the surface of the magnetic working electrode through magnetic force, and completing the lead ion concentration detection.

[0014] Optionally, the magnetic composite material is used as an electrode modification material for the detection of lead ions, comprising the following steps: modifying the magnetic composite material on a magnetic working electrode of an electrochemical sensor, and then completing the detection of the lead ion concentration of the test liquid through the electrochemical sensor.

[0015] In a fourth aspect, the present invention provides an electrochemical sensor for lead ion detection, the electrochemical sensor comprising a working electrode, the substrate of the working electrode being modified with the above-mentioned magnetic composite material; the substrate is a magnetic glassy carbon electrode, the magnetic composite material is located on the working surface of the substrate to form a CoFe2O4@ZIF-67 structural layer; the magnetic glassy carbon electrode and the CoFe2O4@ZIF-67 structural layer form a CoFe2O4@ZIF-67 / GCE working electrode.

[0016] Optionally, the outer surface of the CoFe2O4@ZIF-67 structural layer is coated with a Nafion membrane layer to form a CoFe2O4@ZIF-67 / Nafion / GCE working electrode.

[0017] In a fifth aspect, the present invention provides a method for preparing the above-mentioned electrochemical sensor, which includes a magnetic composite material modification step: dispersing the powder of the magnetic composite material described in claim 1 in deionized water to form a suspension, and then dropwise coating the suspension on the polished surface of a magnetic glassy carbon electrode, and preparing a CoFe2O4@ZIF-67 / GCE working electrode after drying.

[0018] Optionally, the method for making an electrochemical sensor further comprises a protective material modification step: drop-coating a Nafion membrane solution on the surface of the CoFe2O4@ZIF-67 / GCE working electrode, and preparing a CoFe2O4@ZIF-67 / Nafion / GCE working electrode after drying.

[0019] In a sixth aspect, the present invention provides an electrochemical device for lead ion detection, comprising a shell, a micro electrochemical workstation, a liquid feeding device and the electrochemical sensor according to claim 6 or 7; the shell is provided with a detection chamber, a mounting cavity, a liquid inlet and a material port; the liquid feeding device is installed and fixed to the mounting cavity, and the liquid inlet end of the liquid feeding device is connected to the liquid inlet, and the liquid outlet end of the liquid feeding device is connected to the detection chamber; the micro electrochemical workstation is arranged in the shell and connected to the electrochemical sensor; the electrochemical sensor also includes a reference electrode and a counter electrode, and the working electrode, the reference electrode and the counter electrode are arranged in the detection chamber; the material port is connected to the detection chamber, and the material port has an open state and a closed state.

[0020] The technical solution adopted by the present invention can achieve the following beneficial effects:

[0021] In the magnetic composite material, preparation method and application, electrochemical sensor and device disclosed in the present invention, the magnetic composite material has a core-shell structure of CoFe2O4@ZIF-67; wherein the magnetic core body CoFe2O4 is spherical with a rough surface, and its rough surface is composed of a regular cubic structure and irregular small particles, thereby effectively increasing the specific surface area of ​​the core body to provide sufficient coating sites for ZIF-67, so that ZIF-67 is densely wrapped on the surface of the core body in the form of small particles, and the appearance of ZIF-67 is a regular dodecahedron, such structural characteristics avoid The agglomeration problem of ZIF-67 is solved, and a more ideal core-shell structure is presented; therefore, compared with the existing electrode modification materials, the magnetic composite material disclosed in the present invention has a larger specific surface area, can effectively increase its contact area with the electrolyte, and provide more abundant active centers, which is beneficial to the adsorption of lead ions, and better improves the electrochemical performance, so that the electrochemical sensor constructed by it has high detection sensitivity and strong anti-interference ability, and the anions, cations and other impurities in the solution to be tested basically do not interfere with the detection of the electrochemical sensor, and can specifically detect lead ions in the aqueous solution. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0023] Figure 1 A microscopic surface morphology diagram of the magnetic composite material disclosed in the present invention;

[0024] Figure 2 CV diagrams of different modified electrodes;

[0025] Figure 3 DPV curves of different modified electrodes;

[0026] Figure 4 The test results of the stability (a) and reproducibility (b) of the electrochemical sensor disclosed in the present invention;

[0027] Figure 5 The anti-interference performance test structure of the electrochemical sensor disclosed in the present invention;

[0028] Figure 6 It is a schematic structural diagram of the electrochemical device disclosed in the present invention;

[0029] Figure 7 is the test results and linear equation of the experimental samples;

[0030] Description of reference numerals:

[0031] 100 - housing, 101 - liquid inlet, 102 - detection chamber, 110 - filtering structure, 120 - micro peristaltic pump, 121 - one-way valve, 130 - working electrode, 140 - reference electrode, 150 - counter electrode, 160 - micro electrochemical workstation. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the specific embodiments of the present invention and the corresponding drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0033] The technical solutions disclosed in various embodiments of the present invention are described in detail below in conjunction with the accompanying drawings.

[0034] Example 1

[0035] Preparation and characterization of magnetic composite material CoFe2O4@ZIF-67

[0036] Solution A was prepared by dispersing 0.2 g of CoFe2O4 and 7 g of dimethylimidazole in 50 mL of methanol solution.

[0037] 3 g of Co(NO3)2·6H2O was added to 50 mL of methanol solution to prepare solution B. Then, solution A was stirred and solution B was slowly added dropwise to solution A at a uniform rate. After the addition was completed, stirring was continued for 1 hour to prepare a uniformly mixed reaction solution C.

[0038] The uniformly mixed reaction solution was transferred to a 100 mL polytetrafluoroethylene-lined reactor and reacted at 75 °C for 135 min through a hydrothermal reaction. After the reaction was completed, the reactor was naturally cooled to room temperature. The precipitated product after the reaction was magnetically separated and collected by a magnet, and the precipitate was washed with ethanol and dried at 60 °C for 6 h to prepare the CoFe2O4@ZIF-67 magnetic composite material; CoFe2O4 (cobalt tetraoxide ferrite) was the magnetic core and ZIF-67 (zeolite imidazole framework-67) was the shell.

[0039] The prepared CoFe2O4@ZIF-67 magnetic composite material was characterized by scanning electron microscopy; the microscopic surface morphology and particle size distribution results of the magnetic core CoFe2O4 and the magnetic composite material CoFe2O4@ZIF-67 with a core-shell structure are shown in Figure 1 shown.

[0040] Depend on Figure 1 (a) It can be seen that the magnetic core CoFe2O4 is spherical with a rough surface. Figure 1 (b) It can be seen that the rough surface of the magnetic core CoFe2O4 is composed of regular cubic structures and irregular small particles, which can effectively increase the specific surface area of ​​the core and provide sufficient coating sites for ZIF-67; Figure 1 (c) It can be seen that ZIF-67 is densely packed on the surface of the core layer in the form of small particles. Figure 1 (d) It can be seen that the appearance of ZIF-67 is a regular dodecahedron distributed on the surface of the magnetic core CoFe2O4. This structural feature avoids the agglomeration problem of ZIF-67 and presents a more ideal core-shell structure.

[0041] Therefore, the magnetic composite material disclosed in this embodiment can effectively increase the specific surface area of ​​the material through the core-shell structure of CoFe2O4@ZIF-67, thereby increasing its contact area with the electrolyte and providing more abundant active centers, which is beneficial to the adsorption of lead ions and improving the electrochemical performance; at the same time, the preparation method disclosed in this embodiment has the advantage of simple operation.

[0042] Example 2

[0043] The preparation of a working electrode for an electrochemical sensor comprises the following steps:

[0044] A magnetic glassy carbon electrode (GCE) was polished on suede with 1.0μm, 0.3μm and 0.05μm polishing powders respectively, and then ultrasonically cleaned with distilled water and anhydrous ethanol alternately; then, the washed glassy carbon electrode was placed in a 0.5mol / L H2SO4 solution for activation by cyclic voltammetry (CV); the activated glassy carbon electrode was placed in a 5mmol / L K3[Fe(CN)6] solution (containing KCl, concentration of 0.1mol / L) for CV testing, and within the voltage range of -0.2 to 0.8V, the difference in redox peak potential did not exceed 80mV, indicating that the treated glassy carbon electrode; it should be noted that the magnetic glassy carbon electrode is an electrode with an existing structure, also known as a magnetic glassy carbon electrode, which usually has a magnetic structural member such as a magnet arranged inside or at the end of the glassy carbon electrode.

[0045] The CoFe2O4@ZIF-67 magnetic composite material prepared in Example 1 was ground into powder and dispersed in deionized water to prepare a suspension. The suspension was then drop-coated on the treated surface of the magnetic glassy carbon electrode and placed under an infrared lamp to dry. After drop-coating and drying, a CoFe2O4@ZIF-67 / GCE working electrode was prepared.

[0046] Preferably, in order to prevent the CoFe2O4@ZIF-67 adsorbed and fixed on the working surface of the magnetic glassy carbon electrode by magnetic force from falling off, a Nafion (perfluorosulfonic acid resin) membrane can also be coated on the surface of the above-mentioned CoFe2O4@ZIF-67 / GCE working electrode, so that the coated Nafion membrane can play a good protective and reinforcing role for the CoFe2O4@ZIF-67 material adsorbed and fixed on the electrode surface, which is beneficial to prolonging the service life of the CoFe2O4@ZIF-67 / GCE working electrode.

[0047] The specific steps are: drop-coat the Nafion membrane solution (mass fraction of 5%) on the surface of the CoFe2O4@ZIF-67 / GCE working electrode, and place it under an infrared lamp to dry, and after drop-coating and drying, a CoFe2O4@ZIF-67 / Nafion / GCE working electrode is prepared; it should be noted that the Nafion membrane solution is an existing product, which can be purchased directly on the market, and will not be described in detail in this embodiment.

[0048] Example 3

[0049] Electrochemical performance test

[0050] The electrochemical performance test was evaluated by an external CHI660E electrochemical workstation; wherein, the CoFe2O4@ZIF-67 / GCE prepared in Example 2 was used as the working electrode, Ag / AgCl was used as the reference electrode, and the platinum wire was used as the counter electrode. The three electrodes were respectively connected to the corresponding three electrode terminals of the CHI660E electrochemical workstation to carry out CV test and differential pulse voltammetry (DPV) test.

[0051] The CV test was performed in an electrolyte of 5 mmol / L K3[Fe(CN)6] solution (containing KCl at a concentration of 0.1 mol / L), with a voltage range of -0.2 to 0.8 V and a scan rate of 50 mV / s. The differential pulse voltammetry (DPV) test was performed in an electrolyte containing Pb 2+ The test was completed in an electrolyte (0.1 mol / L HAc-NaAc (ABS) buffer solution), with a test potential range of -0.9 to -0.1 V, an amplitude of 50 mV, and a pulse width of 0.2 s; all experimental operations were performed at room temperature. At the same time, CV tests and DPV tests were used to compare the electrochemical performance of different modified electrodes: Bare / GCE, ZIF-67 / GCE, CoFe2O4 / GCE, and CoFe2O4@ZIF-67 / GCE.

[0052] like Figure 2The CV test curves of each electrode are shown. The test results show that compared with the bare electrode Bare / GCE, the redox peaks of ZIF-67 / GCE, CoFe2O4 / GCE and CoFe2O4@ZIF-67 / GCE have increased; and according to the larger redox peak area and the smaller redox potential difference, the conductivity of the electrochemical surface, that is, CoFe2O4 / GCE has the best conductivity, CoFe2O4@ZIF-67 / GCE has better conductivity than ZIF-67 / GCE and is close to that of CoFe2O4 / GCE, and Bare / GCE has the worst conductivity; in addition, the peak value ratio of the oxidation peak current to the reduction peak current of CoFe2O4@ZIF-67 / GCE is also close to 1, indicating that it also has good electron transfer reversibility.

[0053] like Figure 3 The DPV test curves of each electrode are shown. The test results show that the current response signal of CoFe2O4@ZIF-67 / GCE is significantly improved compared with Bare / GCE, CoFe2O4 / GCE and ZIF-67 / GCE. This is because the -COOH, -OH and other functional groups on the surface of CoFe2O4@ZIF-67 can effectively adsorb Pb 2+ , and the contact surface of the composite material is increased, providing more adsorption active sites, which can effectively accumulate Pb 2+ , making more Pb 2+ Deposited on the electrode surface, thereby enhancing the electrochemical response performance.

[0054] At the same time, the DPV test also added a comparative study of the electrode performance of CoFe2O4@ZIF-67 / Nafion / GCE. Figure 3 From the test curve, it can be seen that the current response signal of CoFe2O4@ZIF-67 / Nafion / GCE is better than that of CoFe2O4@ZIF-67 / GCE.

[0055] Example 4

[0056] Stability and reproducibility testing

[0057] CoFe2O4@ZIF-67 / Nafion / GCE was prepared in the presence of 1×10 -5 mol / L Pb 2+ DPV tests were conducted seven times a week in an electrolyte (0.1 mol / L ABS buffer, pH = 4.5). The test results are as follows Figure 4 As shown in (a) and (b) in .

[0058] Among them, according to Figure 4 (a) It can be seen that within a week, Pb2+ The peak current gradually decreased, which may be due to a small amount of material loss during repeated experiments and storage of electrodes, so the peak current showed a downward trend, but its current response remained above 93.1% of the initial current, and the current response after one week could still maintain 91.10% of its initial current, which shows that CoFe2O4@ZIF-67 / Nafion / GCE has good stability; according to Figure 4 (b) It can be seen that CoFe2O4@ZIF-67 / Nafion / GCE The seven measurement results are basically similar, which shows that the electrode modified with this material has good reproducibility.

[0059] At the same time, the same method was used to test the stability and reproducibility of CoFe2O4@ZIF-67 / GCE. The test results showed that CoFe2O4@ZIF-67 / GCE also had good stability and reproducibility, but it was slightly worse than CoFe2O4@ZIF-67 / Nafion / GCE. This may be because the CoFe2O4@ZIF-67 material was adsorbed and fixed on the surface of the magnetic glassy carbon electrode by magnetic force, so a small amount of material would be detached over time, resulting in reduced electrode performance. 。

[0060] Implemented 5

[0061] Anti-interference test

[0062] In actual testing, there are often many interfering ions and Pb in the test solution. 2+ Therefore, the anti-interference ability of CoFe2O4@ZIF-67 / GCE was tested in this example. -5 mol / L Pb 2+ 50 times of Zn 2+ 、Ni 2+ , Fe 3+ 、Co 2+ , Mn 2+ Cr 3+ , 20 times of Cd 2 + , Cu 2+ and 10 times Hg 2+ Perform DPV test, the measurement structure is as follows Figure 5 shown.

[0063] according to Figure 5 The change of DPV current intensity in the Cu 2+ Pb 2+The effect of Cu 2+ With Pb 2+ There is a competitive relationship, Cu 2+ will rob the active sites on CoFe2O4@ZIF-67 / GCE, thus making Pb 2+ The current response of Zn 2+ 、Ni 2+ , Fe 3+ 、Co 2+ , Mn 2+ Cr 3+ 、Cd 2+ Metal ions such as Pb 2+ The influence of the current response is small, and the change of the current response is less than 5%. Therefore, it shows that CoFe2O4@ZIF-67 / GCE has good anti-interference performance and has good 2+ Has good specificity.

[0064] Example 6

[0065] Please refer to Figure 6 The embodiment discloses an electrochemical device, which includes: a shell 100, a micro electrochemical workstation 160, a liquid feeding device and an electrochemical sensor; the shell 100 is provided with a detection chamber 102, a mounting cavity and a liquid inlet 101; the mounting cavity provides a setting space for the installation and fixation of the liquid feeding device in the shell 100, so that the liquid feeding device can be installed and fixed in the mounting cavity to achieve a hidden setting.

[0066] At the same time, the liquid inlet end of the liquid delivery device is connected to the liquid inlet 101, and the liquid outlet end of the liquid delivery device is connected to the detection chamber 102, and the liquid to be tested can be delivered to the detection chamber 102 through the liquid delivery device. Generally, the liquid delivery device can use an existing micro water pump, but preferably uses a micro peristaltic pump 120, so that not only the automatic delivery of the liquid to be tested can be achieved, but also the delivery amount of the liquid to be tested can be accurately controlled, which is conducive to improving the accuracy of the detection structure.

[0067] The micro electrochemical workstation 160 is arranged in the shell 100 and connected to the electrochemical sensor; the electrochemical sensor is a three-electrode system, which includes a reference electrode 140, a counter electrode 150 and a working electrode 130; specifically, the working electrode 130 is the above-mentioned CoFe2O4@ZIF-67 / Nafion / GCE electrode, the reference electrode 140 is the existing Ag / AgCl electrode, and the counter electrode 150 is the existing platinum wire electrode.

[0068] The working electrode 130 allows the test liquid sent into the detection chamber 102 to undergo relevant electrochemical reactions, and in conjunction with the reference electrode 140 and the counter electrode 150, the micro-electrochemical workstation 160 is used to achieve qualitative and quantitative analysis of lead ions; it should be noted that the structure and principle of the above-mentioned micro-electrochemical workstation 160 belong to the prior art and will not be described in detail.

[0069] The housing 100 is also provided with a material port, which is connected to the detection chamber 102 and has an open state and a closed state. The structure of the material port for switching the open state and the closed state can adopt an existing opening and closing structure such as a rotating or sliding type, which will not be described in detail in this embodiment. When the material port is in the open state, it can be used to discharge the liquid to be tested in the detection chamber 102 through the material port and to add a buffer solution into the detection chamber 102 through the material port, such as a phosphate buffer solution or an ABS buffer solution.

[0070] In order to avoid the influence of impurities in the test liquid on the test results, a filtering structure 110, such as a filter net or a filter membrane, can be preferably set at the liquid inlet 101. In order to ensure the filtering effect, the number of layers can be multiple; and in order to avoid the influence of back suction and other phenomena on the liquid delivery accuracy of the micro peristaltic pump 120, a one-way valve 121 is preferably set at the liquid outlet end of the micro peristaltic pump 120. The one-way valve 121 can ensure the normal delivery of the test liquid from the micro peristaltic pump 120 to the detection chamber 102, and prevent the backflow of the test liquid from the detection chamber 102 to the micro peristaltic pump 120.

[0071] It should be noted that, as another possible implementation method, the CoFe2O4@ZIF-67 / Nafion / GCE working electrode in this embodiment can also be replaced by a CoFe2O4@ZIF-67 / GCE working electrode, but the service life of the working electrode will be reduced to a certain extent.

[0072] Example 7

[0073] The electrochemical device in Example 6 was used to measure the Pb in the actual sample. 2+ The concentration was tested, and the spike recovery rate was used as the judgment standard. The specific processing process is as follows:

[0074] Selection of test solution: After the lake or river water is still for 48 hours, the upper clear liquid is taken, and part of the upper clear liquid is filtered through a 0.22m filter membrane and then the lead ion content in the actual sample is detected by ICP-OES; part of the upper clear liquid is diluted 20 times with ABS (pH = 4.5) buffer and prepared into 1 mol / L Pb by the spike method. 2+ and 10 mol / L Pb 2+ The sample is used as the test solution for concentration measurement.

[0075] Detection process: open the one-way valve 121, start the peristaltic pump to absorb a certain amount of detection liquid into the detection chamber 102; then, turn off the peristaltic pump switch, and then close the one-way valve 121, and allow the working electrode in the detection chamber 102 to fully adsorb and combine with the test liquid; after sufficient adsorption, release the excess test solution through the material port, and add buffer to the detection chamber 102 to keep the pH of the detection environment stable to avoid the subsequent detection results being affected by pH changes; then, turn on the micro electrochemical workstation 160 to detect the lead ion concentration; according to the heavy metal ion Pb 2+ The relationship between concentration and peak current change is used to construct a linear regression equation to obtain the concentration of heavy metal ions Pb in the test solution.

[0076] Test results: Figure 7 As shown, the electrochemical device was used to 2+ The spiked concentration test results were basically consistent with the ICP-OES test results. The linear equation was I (μA) = 1.36978c (μM) + 0.38326, the linear correlation coefficient was 0.99996, and the calculated detection limit (LOD) was 9.3738 × 10 -9 M (S / N = 3), sensitivity is 32.17μA·mM -1 cm -2 The recovery rates of river water and lake water were between 99.51% and 103.42%, and the RSD values ​​were all less than 5%. Therefore, it is shown that it can accurately detect Pb in actual samples. 2+ It has broad application prospects.

[0077] The above embodiments of the present invention focus on the differences between the various embodiments. As long as the different optimization features between the various embodiments are not contradictory, they can be combined to form a better embodiment. Considering the simplicity of the text, they will not be repeated here.

[0078] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.

Claims

1. A magnetic composite material, characterized in that: The magnetic composite material has a core-shell structure of CoFe2O4@ZIF-67, wherein CoFe2O4 is a magnetic core and ZIF-67 is a shell.

2. A method for preparing the magnetic composite material according to claim 1, characterized in that: The following steps are involved: (1) Dispersing CoFe2O4 and dimethylimidazole in a methanol solution to prepare solution A; adding Co(NO3)2·6H2O to the methanol solution to prepare solution B; Then, under stirring, the solution B is added dropwise to the solution A, and after being mixed evenly, a reaction solution C is obtained; (2) The reaction solution C is transferred to a reactor for hydrothermal reaction. After the reaction is completed, the reactor is naturally cooled to room temperature, and the precipitate is collected by magnetic separation; the precipitate is then washed with ethanol and dried to prepare the CoFe2O4@ZIF-67 composite material.

3. The magnetic composite material according to claim 1, characterized in that: Application of the magnetic composite material in lead ion detection.

4. The magnetic composite material according to claim 3, characterized in that: The magnetic composite material is used as an additive for lead ion detection, comprising the following steps: adding the magnetic composite material to a test liquid for mixing, starting an electrochemical sensor after the magnetic composite material fully adsorbs the lead ions in the test liquid, and the magnetic working electrode of the electrochemical sensor adsorbs and fixes the magnetic composite material adsorbed with lead ions on the surface of the magnetic working electrode through magnetic force, and completing lead ion concentration detection.

5. The magnetic composite material according to claim 3, characterized in that: The magnetic composite material is used as an electrode modification material for lead ion detection, comprising the following steps: modifying the magnetic composite material on a working electrode of an electrochemical sensor, and then placing the electrochemical sensor in a test solution to complete lead ion concentration detection.

6. An electrochemical sensor for lead ion detection, the electrochemical sensor comprising a working electrode, characterized in that: The substrate of the working electrode is modified with the magnetic composite material according to claim 1; the substrate is a magnetic glassy carbon electrode, and the magnetic composite material is located on the working surface of the substrate to form a CoFe2O4@ZIF-67 structural layer; the magnetic glassy carbon electrode and the CoFe2O4@ZIF-67 structural layer form a CoFe2O4@ZIF-67 / GCE working electrode.

7. The electrochemical sensor for lead ion detection according to claim 6, characterized in that: The outer surface of the CoFe2O4@ZIF-67 structural layer is coated with a Nafion film layer to form a CoFe2O4@ZIF-67 / Nafion / GCE working electrode.

8. A method for manufacturing an electrochemical sensor, characterized in that: The method comprises the steps of modifying the magnetic composite material: dispersing the powder of the magnetic composite material according to claim 1 in deionized water to prepare a suspension, then applying the suspension dropwise to the surface of a polished magnetic glassy carbon electrode, and preparing a CoFe2O4@ZIF-67 / GCE working electrode after drying.

9. The method for manufacturing an electrochemical sensor according to claim 8, characterized in that: The method also includes a protective material modification step: drop-coating the Nafion membrane solution on the surface of the CoFe2O4@ZIF-67 / GCE working electrode, and preparing the CoFe2O4@ZIF-67 / Nafion / GCE working electrode after drying.

10. An electrochemical device for lead ion detection, characterized in that: It comprises a shell, a micro electrochemical workstation, a liquid feeding device and the electrochemical sensor according to claim 6 or 7; the shell is provided with a detection chamber, a mounting cavity, a liquid inlet and a material port; the liquid feeding device is fixed to the mounting cavity, and the liquid inlet end of the liquid feeding device is connected with the liquid inlet, and the liquid outlet end of the liquid feeding device is connected with the detection chamber; the micro electrochemical workstation is arranged in the shell and connected with the electrochemical sensor; the electrochemical sensor also comprises a reference electrode and a counter electrode, and the working electrode, the reference electrode and the counter electrode are arranged in the detection chamber; the material port is connected with the detection chamber, and the material port has an open state and a closed state.

Citation Information

Patent Citations

  • Electrochemical sensor for simultaneously detecting cadmium and lead ions and preparation method

    CN104020213A

  • Three-electrode type Pb(II) electrochemical sensor, preparation method thereof and application thereof

    CN109557153A

  • Detection method of iron-based spinel for heavy metal ion electrochemical sensor

    CN110441365A

  • Catalyst for preparing fructose from glucose and synthesis method thereof

    CN112742479A

  • Carbon material coated spinel iron oxide in-situ growth MOFs adsorption catalytic complex as well as preparation method and application thereof

    CN112844320A